Risk of Cervical Intra-epithelial Neoplasia and Invasive Cancer of the Cervix in DES Daughters. Issue 10 (October 2017) - Verloop, J.; van Leeuwen, F. E.; Helmerhorst, Th. J. M.; de Kok, I. M. C. M.; van Erp, E. J. M.; van Boven, H. H.; Rookus, M. A.
Abstract : (Abstracted from Gynecol Oncol 2017;144:305–311) Several million pregnant women worldwide received diethylstilbestrol (DES) from the late 1940s to the early 1970s to prevent miscarriages and other pregnancy complications. Women exposed to DES in utero have an increased risk of clear cell adenocarcinoma (CCA) of the vagina and cervix; their risk of non–CCA-invasive cervical cancer remains unclear.